Are young people's educational outcomes linked to their sense of control? - Baron, Juan D.; Clark, Deborah Cobb (2010)
This paper analyzes the link between young people's sense (locus) of control over their lives and their investments in education. We find that young people with a more internal locus of control have a higher probability of finishing secondary school and, conditional on completion, meeting the requirements to obtain a university entrance rank. Moreover, those with an internal locus of control who obtain a university entrance rank achieve somewhat higher rankings than do their peers who have a more external locus of control. Not surprisingly, there is a negative relationship between growing up in disadvantage and educational outcomes. However, this effect does not appear to operate indirectly by increasing the likelihood of having a more external locus of control. In particular, we find no significant relationship between family welfare history and young people's locus of control.